Penerapan Pidana Adat terhadap Anak sebagai Pelaku Perusakan Kekayaan Adat dan Lingkungan - Ari Muhammad (CV Rewang Rencang, 2025)
Cultural wealth is an asset that cannot be separated from the identity of indigenous peoples and must be preserved. Currently, juvenile delinquency poses a risk to cultural wealth, whether it pertains to sacred matters, culture, or other forms of cultural wealth. In the Criminal Accountability System for Children in Conflict with the Law (ABH), children can be held responsible through a more restorative justice approach in its resolution. This paper examines the application of customary criminal law to children as perpetrators of the destruction of cultural wealth, viewed from the perspective of customary criminal law. The study results indicate that the application of customary criminal law to children who destroy cultural wealth can be held accountable according to the customary rules where they committed the offense, and the penalty will depend on the decision made by the customary leader/institution regarding the actions causing damage to cultural wealth.